Greening the Organic Supply Chain in the Context of Relationship Management - Kłosińska , Joanna; Raźniewska , Marta; Sosnowski , Piotr (Studia Oeconomica Posnaniensia, 2018)
The aim of this article is to determine the role of relationship management in the context of greening the organic supply chain. The introduction of environmental activities in supply chain management is a current topic due to the increasing environmental awareness of final customers. Nowadays, the customer is the central link around which economic activity takes place. As it is an inseparable element of a company’s success and its market position, it is necessary to compete by taking care of customer satisfaction and loyalty in order to build long-term customer relationships which might be dependent on relationships with suppliers. Firstly, the concept of greening the organic supply chain is presented. Secondly, the possible role of relationship management is outlined. The authors focus on relationships with suppliers and customers with special interest on the perspective of organic food distribution companies. Next, the research methodology is described. Finally, the results, conclusions and recommendations for future research are given. Anticipated results refer to premises of greening the organic supply chain in the context of managing relationships with suppliers and customers. The following scientific methods were used: literature analysis and a survey performed using a Computer Assisted Telephone Interview and an Individual In-depth Interview.